Effect of Low-Dose Radiotherapy on the Circulating Levels of Paraoxonase-1-Related Variables and Markers of Inflammation in Patients with COVID-19 Pneumonia - Elisabet Rodríguez-Tomàs; Johana C. Acosta; Laura Torres-Royo; Gabriel De Febrer; Gerard Baiges-Gaya; Helena Castañé; Andrea Jiménez; Carlos Vasco; Pablo Araguas; Junior Gómez; Bárbara Malave; Miguel Árquez; et al. (MDPI AG, 2022)
The aim of our study was to investigate the changes produced by low-dose radiotherapy (LDRT) in the circulating levels of the antioxidant enzyme paraoxonase-1 (PON1) and inflammatory markers in patients with COVID-19 pneumonia treated with LDRT and their interactions with clinical and radiological changes. Data were collected from the IPACOVID prospective clinical trial (NCT04380818). The study included 30 patients treated with a whole-lung dose of 0.5 Gy. Clinical follow-up, as well as PON1-related variables, cytokines, and radiological parameters were analyzed before LDRT, at 24 h, and 1 week after treatment. Twenty-five patients (83.3%) survived 1 week after LDRT. Respiratory function and radiological images improved in survivors. Twenty-four hours after LDRT, PON1 concentration significantly decreased, while transforming growth factor beta 1 (TGF-β1) increased with respect to baseline. One week after LDRT, patients had increased PON1 activities and lower PON1 and TGF-β1 concentrations compared with 24 h after LDRT, PON1 specific activity increased, lactate dehydrogenase (LDH), and C-reactive protein (CRP) decreased, and CD4+ and CD8+ cells increased after one week. Our results highlight the benefit of LDRT in patients with COVID-19 pneumonia and it might be mediated, at least in part, by an increase in serum PON1 activity at one week and an increase in TGF-β1 concentrations at 24 h.